A Radicular Cyst With Extensive Bone Loss Requires Surgical and Endodontic Management: Case Presentation and Literature Review - Juan Martín Pesántez Alvarado; Milton Fabricio Lafebre Carrasco (Case Reports in Dentistry)
The radicular cyst is an inflammatory pathology affecting the periapical bone tissue associated with teeth exhibiting pulp necrosis. Without timely endodontic intervention, this pathology can lead to significant bone tissue destruction due to its growth pattern, necessitating both endodontic and surgical approaches to halt its progression and remove the involved tissue. This case study details the management of a 23-year-old patient with a history of prior trauma, presenting with pressure in the anterior maxillary region. Tomographic examination revealed a hypodense area involving Teeth 2.1, 2.2, and 2.3. A surgical approach involving enucleation and endodontic treatment was undertaken. The diagnosis was confirmed histopathologically, and follow-up radiographs demonstrated satisfactory bone filling.